Ecological Risk Assessment of Organochlorine Pesticide in the Al-Diwaniyah River (Journal of University of Babylon for Engineering Sciences, 2024)
This study aims to calculate the Risk of organochlorine pesticides on the environment residues in the surface waters of Al- Diwaniyah River. Three organochlorine pesticides were targeted (4,4′-DDT, heptachlor, and endosulfan). Ten samples were taken during the pesticide application period from the beginning, middle, and end of the river in the October, the air temperature was 40 degrees Celsius, and the samples were analyzed using Gas chromatography device and the concentration of 4,4′-DDT was from (0.02-0.06 µg/L), heptachlor was from (0.34-0.59 µg/L) and endosulfan was from (0.002-0.03 µg/L). Using the risk quotient method, the ecological risk of these pesticides was calculated, 4,4′-DDT was classified as low risk 0.01≤RQ